Additional and new lichen records from Cozia National Park, Romania - ÇOBANOĞLU, GÜLŞAH (MYCOTAXON LTD, 2010)
A list of 115 lichen taxa from Cozia National Park includes 8 new records for the mycota of Romania and 77 taxa new for Cozia. Distribution and substrata are summarized, and the complete annotated species list is posted at http://www.mycotaxon.com/resources/weblists.html
Keywords: lichenized fungi; biodiversity; biota; checklist; Cozia Mount